2019
DOI: 10.1111/1756-185x.13782
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expansion of circulating CD4+CXCR5+CCR7loPD1hi Tfh precursor cells in idiopathic inflammatory myopathy

Abstract: Objective To determine circulating follicular T helper (Tfh) cell precursor and its relationship with clinical characteristics in idiopathic inflammatory myopathy (IIM). Methods The study population included 47 patients with IIM and 30 healthy controls. Circulating CD4+CXCR5+CCR7loPD‐1hi T cells and intracellular interleukin (IL)‐21 were assessed by flow cytometry. Serum IL‐21 levels were measured by enzyme‐linked immunosorbent assay. The disease activity was evaluated using myositis disease activity assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Moreover, we characterized the immune microenvironment of IIM. Consistent with previous findings, there was a substantial infiltration of pro-inflammatory immune cells in the IIM group (follicular helper T cells, gamma delta T cells, and M1 macrophages) and a clear lack of suppressive inflammatory cells (Tregs) compared to the HC group ( 65 67 ). Correlation analysis revealed that key genes were linked to multiple immune-infiltrating cells, indicating that key genes may be involved in the progression of IIM by regulating immune cells.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we characterized the immune microenvironment of IIM. Consistent with previous findings, there was a substantial infiltration of pro-inflammatory immune cells in the IIM group (follicular helper T cells, gamma delta T cells, and M1 macrophages) and a clear lack of suppressive inflammatory cells (Tregs) compared to the HC group ( 65 67 ). Correlation analysis revealed that key genes were linked to multiple immune-infiltrating cells, indicating that key genes may be involved in the progression of IIM by regulating immune cells.…”
Section: Discussionsupporting
confidence: 91%
“…It has also been revealed that higher percentages of CD4þCXCR5þCCR7loPD-1hi T cells were associated with higher disease activity scores assessed by PGA and higher serum creatine kinase levels. In addition, the percentage of circulating CD4þCXCR5þ CCR7loPD-1hi T cells decreased significantly after successful treatment [25]. These findings indicate that CD4þCXCR5þCCR7loPD-1hi T cells may be a disease activity marker in polymyositis/dermatomyositis patients.…”
Section: Circulating T-cell Subsets As Disease Activity In Dermatomyo...mentioning
confidence: 74%
“…Moreover, several studies attempted to identify new T-cell subsets in myositis patients and correlated the subsets' abnormalities with disease activities. Zhang et al [25] investigated a Tfh cell-like circulating T-cell subsets, CD4þCXCR5þCCR7loPD-1hi T cells, in polymyositis and dermatomyositis patients and found that this subset of T cells was significantly increased in polymyositis/dermatomyositis patients. It has also been revealed that higher percentages of CD4þCXCR5þCCR7loPD-1hi T cells were associated with higher disease activity scores assessed by PGA and higher serum creatine kinase levels.…”
Section: Circulating T-cell Subsets As Disease Activity In Dermatomyo...mentioning
confidence: 99%
“…Multiple studies have reported an increase in circulating Tfh cells in patients with idiopathic inflammatory myopathies, particularly Tfh2 and Tfh17 14 79–81. In the affected muscle tissue of patients with dermatomyositis, infiltration of Tph cells and clustering of B cells around it have been observed, suggesting that Tph cells may be involved in the enhancement and persistence of autoimmune responses at peripheral inflammatory sites 82.…”
Section: Tfh and Tph Cells In Rheumatic And Musculoskeletal Diseasesmentioning
confidence: 99%